1973
DOI: 10.1111/j.1365-2621.1973.tb02825.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE UTILIZATION OF COCONUT MEAL A New Enzymic‐Chemical Method for Fiber Free Protein Extraction of Defatted Coconut Flour

Abstract: A simple enzymic‐chemical protein extraction process was developed. Proteases rather than carbohydrases were more efficient for the enzymatic treatment. Dilute NaOH was more effective than dilute HCl for the complementary chemical treatment. The combined treatments were more efficient than each of the two separately. The method devised was equally effective when applied to live coconut meals obtained through different oil extraction techniques. The partial hydrolysis of the protein during the proteolytic enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Coconut proteins generally provide good nutritional value with a relatively balanced amino acid profile (Gonzales & Tanchuco, ; Gunetileke & Laurentius, ; Kwon et al., ; Rasyid et al., ). Those proteins contain a high amount of essential amino acids (71% to 77%) and a digestibility of 86% to 94% (Hagenmaier, Mattil, & Cater, ; Molina & Lachance, ). In coconut skim milk, the limiting amino acids are methionine, isoleucine, threonine, and tryptophan (Hagenmaier, Lopitakwong, & Verasestakul, ).…”
Section: Coconut Proteinsmentioning
confidence: 99%
“…Coconut proteins generally provide good nutritional value with a relatively balanced amino acid profile (Gonzales & Tanchuco, ; Gunetileke & Laurentius, ; Kwon et al., ; Rasyid et al., ). Those proteins contain a high amount of essential amino acids (71% to 77%) and a digestibility of 86% to 94% (Hagenmaier, Mattil, & Cater, ; Molina & Lachance, ). In coconut skim milk, the limiting amino acids are methionine, isoleucine, threonine, and tryptophan (Hagenmaier, Lopitakwong, & Verasestakul, ).…”
Section: Coconut Proteinsmentioning
confidence: 99%
“…Coconut oil is separated from dried coconut meat (''copra'') by pressing copra in an expeller or by solvent extraction. Protein can be extracted from the residue of this process by chemical, enzymatic and enzyme-chemical methods (Chellian & Baptist, 1969;Lachance & Molina, 1974;Molina & Lachance, 1973;Molina, Lachance, & Bressani, 1976). However, the high temperature of the expellers used during the commercial extraction of oil lowers 0963-9969/$ -see front matter Ó 2005 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…The relative insolubility, due to native structure, extraction conditions or denaturation, of some of the plant and animal proteins limits their usefulness in food products. Research has shown that the solubility and/or extractability of proteins of beans (18), rapeseed concentrate (19), alfalfa meal (20), heat denatured cottonseed meal (21) and coconut meal (22) and fish protein concentrate (23) can be enhanced by pro° teolysis.…”
Section: Limited Proteolysismentioning
confidence: 99%